The Political and Military Value of the ""Set Piece"" Killing Tactic in East Tyrone 1983––1992. (1st April 2014) - ,
Abstract : The period from 1983 to 1992 witnessed an intensification of the state use of the Special air Services (SaS) in the deployment of the ""set piece"" killing tactic in Northern Ireland against the Irish Republican army (IRa), a separatist insurgent group embroiled in political conflict in the region. The vast majority of these ""set piece"" killings occurred within the geographical confines of the East Tyrone region and were directed at the IRa's East Tyrone Brigade. This article will argue that the use of the ""set piece"" tactic in East Tyrone was a deliberate security policy choice. In doing so, this article interrogates the political and military value that the tactic had for the state and security forces. This article will identify how and why the tactic came to be implemented in East Tyrone when it did, and why the area appears to have borne the brunt of the tactic while other hotbeds of IRa activity were not targeted in a similar manner. Locating this research in the broader realms of British counter-insurgency it will evaluate what contribution the tactic made to the containment of IRa activity in the East Tyrone area.